Leiomyomas in Pregnancy and Spontaneous Abortion: A Systematic Review and Meta-analysis. Issue 5 (November 2017) - Sundermann, Alexandra C.; Velez Edwards, Digna R.; Bray, Michael J.; Jones, Sarah H.; Latham, Sanura M.; Hartmann, Katherine E.
Abstract : OBJECTIVE: To systematically review studies reporting the risk of spontaneous abortion among pregnant women of typical reproductive potential with and without uterine leiomyomas. DATA SOURCES: We searched PubMed, EMBASE, Web of Science, andClinicalTrials.gov for publications from January 1970 to December 2016. METHODS OF STUDY SELECTION: We excluded studies that did not use imaging to uniformly document leiomyoma status of all participants, did not have a comparison group without leiomyomas, or primarily included women seeking care for recurrent miscarriage, infertility care, or assisted reproductive technologies. TABULATION, INTEGRATION, AND RESULTS: Two authors independently reviewed eligibility, extracted data, and assigned overall quality ratings based on predetermined criteria. Of 1, 469 articles identified, nine were eligible. Five enrolled general obstetric populations and four included women undergoing amniocentesis. In five studies in general obstetric populations that included 21, 829 pregnancies (1, 394 women with leiomyomas and 20, 435 without), only one adjusted for potential confounders. This meta-analysis revealed no increase in risk of spontaneous abortion among those with leiomyomas compared with those without (11.5% compared with 8.0%; risk ratio 1.16, 95% CI 0.80–1.52). When bias from confounding was estimated for nonadjusted studies, the aggregate calculated risk ratio was 0.83 (95% CI 0.68–0.98). CONCLUSION: Leiomyoma presence was not associated with increased risk of spontaneous abortion in an analysis of more than 20, 000 pregnant women. Failure of prior studies to adjust for confounders may have led to the common clinical belief that leiomyomas are a risk factor for spontaneous abortion. Abstract : Leiomyoma presence during pregnancy is not associated with increased risk of spontaneous abortion in general obstetric populations.